2012
DOI: 10.1016/j.jalz.2013.08.035
|View full text |Cite
|
Sign up to set email alerts
|

P4‐253: Hilar GABAergic interneuron activity controls spatial learning and memory retrieval

Abstract: Background: Although extensive research has demonstrated the importance of excitatory granule neurons in the dentate gyrus of the hippocampus in normal learning and memory and in the pathogenesis of amnesia in Alzheimer's disease (AD), the role of hilar GABAergic inhibitory interneurons, which control the granule neuron activity, remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…For example, increased granule cell excitability is observed in hippocampal slices following perforant path stimulation when hilar interneurons are ablated (Ratzliff et al, ). More recently, elevated granule cell firing rates together with increased numbers of cFos‐positive neurons in the DG were observed when hilar GABAergic interneurons were silenced using in vivo optogenetic techniques (Andrews‐Zwilling et al, ). Thus, increasing numbers of activated granule cells following hilar interneuron silencing would diminish the sparse encoding in DG required for optimal pattern separation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, increased granule cell excitability is observed in hippocampal slices following perforant path stimulation when hilar interneurons are ablated (Ratzliff et al, ). More recently, elevated granule cell firing rates together with increased numbers of cFos‐positive neurons in the DG were observed when hilar GABAergic interneurons were silenced using in vivo optogenetic techniques (Andrews‐Zwilling et al, ). Thus, increasing numbers of activated granule cells following hilar interneuron silencing would diminish the sparse encoding in DG required for optimal pattern separation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increasing numbers of activated granule cells following hilar interneuron silencing would diminish the sparse encoding in DG required for optimal pattern separation. Consistent with a loss of such function, optogenetic inhibition of hilar interneurons is sufficient to impair spatial learning and memory in mice (Andrews-Zwilling et al, 2012). Although the dentate hilus contains a functionally heterogeneous population of GABAergic interneurons, SOM-expressing hilar interneurons are uniquely positioned to maintain sparse encoding within the granule cell population via feedback inhibition onto granule cell dendrites in the perforant path termination zone (i.e., hilar perforant pathassociated cell [HIPP cell]; Freund and Buzsaki, 1996;Houser, 2007;Myers and Scharfman, 2009).…”
Section: Potential Impact Of Gad67-and Som-immunoreactive Hilar Intermentioning
confidence: 99%
“…A plethora of studies using optogenetics have begun to causally interrogate neural circuits in cognition and emotion (Tye and Deisseroth, 2012). Optogenetics permit controlling the activity of cell bodies such as DGCs (Kheirbek et al, 2013) or specific hippocampal sub-region afferents systems (Felix-Ortiz et al, 2013;Lovett-Barron et al, 2014) or specific cell populations such as hilar GABA interneurons (Andrews-Zwilling et al, 2012). Combining optogenetics with optical imaging technologies that enable in vivo imaging of cellular assemblies in awake behaving animals (Chen et al, 2013;Ziv et al, 2013;Gunaydin et al, 2014;Chen et al, 2015b;Jennings et al, 2015;Resendez and Stuber, 2015), will permit assessment of the interplay of different cell-types in DG-CA3 microcircuits and cortical neurons in the context of encoding and re-organization of traumatic memories with passage of time.…”
Section: Re-engineering Intrinsic and Extrinsic Connectivity Of The Dmentioning
confidence: 99%
“…The spatial impairment in the cKO mice could also be due to more direct effects of aberrant cholinergic signaling on encoding, retrieval and task performance. Prior studies have shown that hilar interneurons play a critical role in water maze performance, which argues that impaired cholinergic modulation of interneurons could mediate the observed spatial deficit in α7 cKO mice (Andrews-Zwilling et al 2012).…”
Section: Discussionmentioning
confidence: 99%